2008
DOI: 10.1002/humu.20848
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic functional properties of androgen receptor mutants in prostate cancer

Abstract: The androgen receptor (AR) signaling pathway plays an important role during the development of the normal prostate gland, but also during the progression of prostate cancer on androgen ablation therapy. Mutations in the AR gene emerge to keep active the AR signaling pathway and to support prostate cancer cells growth and survival despite the low levels of circulating androgens. Indeed, mutations affecting the ligand binding domain (LBD) of the AR have been shown to generate so-called "promiscuous" receptors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 126 publications
0
50
0
2
Order By: Relevance
“…These authors identified low levels of expression of ARDCTD in AAR PCa xenografts. Interestingly, different point mutations introducing premature stop codons were identified in mRNA extracted from 16% of AAR PCa metastasis (29,(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…These authors identified low levels of expression of ARDCTD in AAR PCa xenografts. Interestingly, different point mutations introducing premature stop codons were identified in mRNA extracted from 16% of AAR PCa metastasis (29,(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that in addition to an autocrine mechanism (37), AR signaling in PCa cells can act on neighboring malignant cells in a paracrine manner (38). To test whether the observed synergy between ERG and AR occurs in a cellautonomous manner, we compared the effect of mixing prostate cells infected separately or coinfected with ERG and AR lentiviruses (Fig.…”
Section: High Levels Of Erg Fully Transform Primary Prostate Cells Thmentioning
confidence: 99%
“…Mutation analysis confirmed that the LBD is essential for DHT-induced nuclear import of eAR and following transactivation function in the nucleus. The LBD mutations were indeed observed in human complete androgen insensitivity syndrome and partial androgen insensitivity syndrome diseases and in prostate cancer (1,2). Evolutionarily, three ␣-helices (eH3, eH4, and eH5) in the LBD are spatially essential for the AR function despite the different amino acid sequence; therefore, the structure of three ␣-helices has been conserved from eels to humans during vertebrate evolution.…”
Section: Discussionmentioning
confidence: 97%
“…3 The activated AR is translocated into the nucleus for a cascade of androgen signaling. AR mutations are frequent in metastatic prostate cancer, and more than 70 single-base substitutions have been described so far in prostate cancer (1,2), which would be one of the main causes of androgen-independent prostate cancer. Although great progress has been made, development of prostate cancer is a complicated process, and its molecular mechanism remains elusive.…”
mentioning
confidence: 99%